Overview of Lymphocyte Count Examination in Patients with Advanced Phase Pulmonary Tuberculosis at Ciamis Regional General Hospital - Istianah, Euis Tia; Firdaus, Selvira Rahma; Wilujeng, Endang Octaviana (LPPM STIKes Muhammadiyah Ciamis, 2025)
Background & Objectives: Pulmonary tuberculosis is a contagious infectious disease caused by Mycobacterium tuberculosis. This infection can be cured through two phases of treatment, namely the intensive phase and the continuation phase. The intensive phase is carried out for two months while the continuation phase is carried out for four months. Tuberculosis treatment is carried out by administering Anti-Tuberculosis Drugs (OAT) consisting of Rifampicin, Ethambutol, Isoniazid, and Pyrazinamide. To monitor the success of treatment and the healing process of tuberculosis, a hematology examination can be done, namely a lymphocyte cell count. In a body infected with bacteria, lymphocyte cells will decrease, after treatment is given, lymphocyte cells will increase or return to normal. The purpose of this study was to see the picture of the results of the lymphocyte count examination in patients with advanced phase pulmonary tuberculosis.Method: This research method is descriptive which was conducted on patients with advanced phase pulmonary tuberculosis at the Ciamis Regional General Hospital in May 2024 with a sample size of 30 respondents. The study used secondary data and primary data which were processed into tables and then explained in narrative. The research was conducted using a hematology analyzer. The research was conducted in May 2024 at the hematology laboratory of the Ciamis Regional General Hospital.Results: From this study obtained the results of 2 (7%) samples with lymphopenia results, as many as 25 (83%) samples with normal lymphocyte results and 3 (10%) samples with lymphocytosis results.Conclusion: The results of the lymphocyte count examination in patients with advanced phase pulmonary tuberculosis found an average normal lymphocyte count.